An Analysis of E-learning Information System Adoption in Ugandan Universities: Case of Makerere University Business School. - Mayoka, Kituyi Geoffrey; Kyeyune, Robert (Information Technology Research Journal, 2012)
This paper presents an examination of e-learning Information Systems failures and adoption problems in Ugandan universities based on Rogers and Shoemaker’s Diffusion of Technological Innovation Theory. Makerere University Business School was used as a case study, where two e-learning systems at Makerere University Business School were surveyed. A self-administered questionnaire was given to 200 respondents who comprised of academic staff, administrative staff and students. The results were analyzed using descriptive statistics. Findings indicate that Assistant Lectures and Lecturers were more willing to adopt to e-learning than their senior counterparts, the Professors. The results also indicate that although students are aware of e-learning, many of them were not comfortable using the technology. The most hideous challenges for e-learning adoption were identified as lack of resources, knowledge and resistance to change. A number of recommendations have been made for faster adoption and use of e-learning information systems at Makerere University Business School and other universities.
Keywords: e-learning; Adoption; Sustainability; Information systems; Uganda